O cinema de Chantal Akerman: estilo e claustrofobia em Saute ma ville (1968) e Jeanne Dielman 23 Quai du Commerce, 1080 Bruxelles (1975) - Silva, Natália Marchiori da (2020)
This research analyzes two films by Belgian filmmaker Chantal Akerman, Saute ma Ville (1968) and Jeanne Dielman, 23 Quai du Commerce, 1080 Bruxelles (1975), with the purpose of investigate the domestic claustrophobia sensation as an authorial trait of Akerman, an element that is referenced all over the filmograpy of the filmmaker. Therefore it is important to highlight the thematic and stylist crossings in the directress’s work. We emphasize along the analysis the montage, the sound use, the performance, the framework and duration of the plan as ways to build a cinema based on sensations. The Akerman’s formal and thematic choices are associate with the questions purpose by modern cinema, in the same time, weembracing the present affinities in her work with the feminist theory. Akerman combines elementes of referentiality to build her own cinema, an authorial cinema, which creates visibilities and fissure that produces sensitive forms of apprehension, and therefore, others critical possibilities to the women’s everyday, the domestic claustrophobia experienced in their daily lives.